Improving antimicrobial use through antimicrobial stewardship in a lower-middle income setting: a mixed-methods study in a network of acute-care hospitals in Viet Nam. (December 2021) - Huong, Vu Thi Lan; Ngan, Ta Thi Dieu; Thao, Huynh Phuong; Tu, Nguyen Thi Cam; Quan, Truong Anh; Nadjm, Behzad; Kesteman, Thomas; Kinh, Nguyen Van; van Doorn, H Rogier
Highlights: Antimicrobial stewardship (AMS) in low- and middle-income settings has multiple players. Leadership commitment greatly influences AMS implementation in hospitals. Staff showed good perception of AMS but misperceptions on local resistance levels. Guidelines on staffing and training standards are needed to support implementation. More support is needed to promote active roles of pharmacists and microbiologists. Abstract: Objectives: This study aimed to analyse the current state of antimicrobial stewardship (AMS) in hospitals in Viet Nam, a lower-middle income country (LMIC), to identify factors determining success in AMS implementation and associated challenges to inform planning and design of future programmes. Methods: We conducted a mixed-methods study in seven acute-care hospitals in the antimicrobial resistance (AMR) surveillance network in Viet Nam. Data collection included 7 focus group discussions, 40 in-depth interviews and a self-administered quantitative survey of staff on AMR and AMS programmes. We summarised qualitative data by reporting the most common themes according to the core AMS elements, and analysed quantitative data using proportions and a linear mixed-effects model. Results: The findings reveal a complex picture of factors and actors involved in AMS implementation from the national level to the departmental and individual level within each hospital. The level of implementation varied, starting from the formation of an AMS committee, with or without active delivery of specific interventions. Development of treatment guidelines, pre-authorisation of antimicrobial drug classes, and post-prescription audit and feedback to doctors in selected clinical departments were the main interventions reported. A higher level of leadership support and commitment to AMS led to a higher level of engagement with AMS activities from the AMS team and effective collaboration between departments involved. Conclusion: Establishing country-specific guidelines on AMS staffing and adapting standards for AMS education and training from international resources are needed to support capacity building to implement AMS programmes effectively in LMICs such as Viet Nam.